2012
DOI: 10.1029/2012gl053577
|View full text |Cite
|
Sign up to set email alerts
|

The reduction of storm surge by vegetation canopies: Three‐dimensional simulations

Abstract: [1] Significant buffering of storm surges by vegetation canopies has been suggested by limited observations and simple numerical studies, particularly following recent Hurricanes Katrina, Rita, and Wilma. Here we simulate storm surge and inundation over idealized topographies using a threedimensional vegetation-resolving storm surge model coupled to a shallow water wave model and show that a sufficiently wide and tall vegetation canopy reduces inundation on land by 5 to 40 percent, depending upon various storm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 21 publications
5
76
0
Order By: Relevance
“…Costanza et al, 2008;Das and Vincent, 2009;Kraus et al, 2009;Gedan et al, 2011) and hydrodynamic modelling studies (e.g. Wamsley et al, 2010;Temmerman et al, 2012;Zhang et al, 2012;Sheng et al, 2012;Liu et al, 2013;Hu et al, 2015). All these studies focussed on the attenuation of storm surges that propagate through coastal wetlands, which we call here within-wetland attenuation, while to our knowledge few scientific studies exist on the effects of intertidal wetland properties on storm tide attenuation along estuaries, a mechanism we call here along-estuary attenuation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Costanza et al, 2008;Das and Vincent, 2009;Kraus et al, 2009;Gedan et al, 2011) and hydrodynamic modelling studies (e.g. Wamsley et al, 2010;Temmerman et al, 2012;Zhang et al, 2012;Sheng et al, 2012;Liu et al, 2013;Hu et al, 2015). All these studies focussed on the attenuation of storm surges that propagate through coastal wetlands, which we call here within-wetland attenuation, while to our knowledge few scientific studies exist on the effects of intertidal wetland properties on storm tide attenuation along estuaries, a mechanism we call here along-estuary attenuation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lovelace, 1994;McGee et al, 2006;Krauss et al, 2009;Wamsley et al, 2010) and on hydrodynamic model simulations (e.g. Resio and Westerink, 2008;Loder et al, 2009;Wamsley et al, 2009Wamsley et al, , 2010Zhang et al, 2012;Temmerman et al, 2012;Sheng et al, 2012;Liu et al, 2013;Hu et al, 2015). These studies reported that peak water levels can be reduced by 5 to 50 cm km −1 when storm surges travel through tidal marshes or mangroves, causing flood wave energy loss due to increased bottom friction.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Sheng et al [52,53] developed a vegetation model which incorporates the effects of vegetation on mean flow and turbulence in the water column. The vegetation resolving model showed that, during hurricanes, total inundation volume can be reduced by up to 40% due to the presence of vegetation.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Meanwhile, mangroves provide habitat for fisheries and are green infrastructures that can protect coastal communities from flooding due to tropical cyclones (e.g., Krauss et al, 2009;Mcivor et al, 2012;Sheng et al, 2012) and tsunamis (Alongi, 2008). Nowadays, the creation and restoration of coastal ecosystems, including mangrove forests, coral reefs, and salt marshes, are being considered by many as a more sustainable, cost-effective and ecologically sound alternative instead of hard infrastructure for the mitigation of future coastal hazards (Feagin, 2008;Gedan et al, 2011;Duarte et al, 2013;Temmerman et al, 2013;Spalding et al, 2014).…”
Section: Introductionmentioning
confidence: 99%